Rejuvenating mind, body, and spirit: Exploring the role of physical activity in health and rehabilitation institutions’ offerings in Serbia - Živković, Ivan; Brdar, Ivana; Knežević, Miroslav (Hotel and Tourism Management, 2024)
Purpose – This paper focuses on physical activity and body care as indicators of wellness offerings in health-rehabilitation institutions in Serbia. The goal is to determine if these institutions can become leaders in the tourism market by providing wellness services. Methodology – A measuring instrument was developed for research purposes. This tool aimed to gather data regarding services associated with physical activity and body care, serving as a crucial indicator of the wellness offerings. Its purpose was to enable the comprehensive evaluation of each center based on the investigated indicator. Findings – After analyzing 20 institutions, Banja Junaković, Ivanjica, and Čigota achieved the highest average score of 0.83, reflecting their comprehensive services and resulting in a final score of 5. Two institutions scored 0.79, coming close to an overall rating of five. All institutions provide programs for assessing the current state of the body. Implications – The study enhances understanding of physical activity and bodily well-being’s significance in advancing health and rehabilitation facilities, aligning with current wellness tourism trends. Results can aid hotel and wellness center managers in the health and wellness tourism industry in refining their business strategies.